Penerapan Prinsip Etika Bisnis dalam Produksi, Distribusi, dan Konsumsi yang Berkelanjutan - Sabri; Amelia; Febrianti, Eka; Asnah; Novita Sari, Rika (Jurnal Indragiri Penelitian Multidisiplin, 2025)
This research examines the application of Islamic business ethics in an increasingly complex business world, particularly in the context of rising consumer consumption. The study focuses on how Islamic principles can guide business actors in their economic activities, from production to consumption. Through a qualitative research method, this study analyzes various literature sources related to Islamic business ethics. The results of the analysis show that there are several fundamental principles that Muslim business actors must uphold, such as the principles of halal, justice, environmental sustainability, trust, and social responsibility. These principles are not merely religious obligations but also have positive implications for business sustainability and societal well-being.The implementation of Islamic business ethics in business practices offers several benefits, including increased consumer trust, competitive advantage, and contributions to sustainable development. Thus, this study concludes that Islamic business ethics provides a comprehensive framework for businesses to operate responsibly and sustainably